2016
DOI: 10.3390/cryst6060073
|View full text |Cite
|
Sign up to set email alerts
|

Control of Cellular Arrangement by Surface Topography Induced by Plastic Deformation

Abstract: Abstract:The anisotropic microstructure of bone tissue is crucial for appropriate mechanical and biological functions of bone. We recently revealed that the construction of oriented bone matrix is established by osteoblast alignment; there is a quite unique correlation between cell alignment and cell-produced bone matrix orientation governed by the molecular interactions between material surface and cells. Titanium and its alloys are one of the most attractive materials for biomedical applications. We previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The reflection of these mechanisms on the material surface, namely, surface relief, can be observed in the SEM and AFM observations. Specifically, it is clearly seen in Figures 3, 4 that the deformation markings protruding out of the material surface modify surface topography significantly and increase surface roughness (Matsugaki et al, 2012;Matsugaki and Nakano, 2016;Uzer et al, 2016). Misorientation angle between the neighboring grains might increase with plastic straining further contributing to the roughness of the samples (Sinha et al, 2015;Srinivasan et al, 2016).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…The reflection of these mechanisms on the material surface, namely, surface relief, can be observed in the SEM and AFM observations. Specifically, it is clearly seen in Figures 3, 4 that the deformation markings protruding out of the material surface modify surface topography significantly and increase surface roughness (Matsugaki et al, 2012;Matsugaki and Nakano, 2016;Uzer et al, 2016). Misorientation angle between the neighboring grains might increase with plastic straining further contributing to the roughness of the samples (Sinha et al, 2015;Srinivasan et al, 2016).…”
Section: Discussionmentioning
confidence: 95%
“…Recently, simple bulk plastic deformation methods (e.g., tension or compression tests) have been utilized to impart micro/nanoscale topography on the metal surface (Matsugaki et al, 2012;Matsugaki and Nakano, 2016;Uzer et al, 2016Nune et al, 2018). These studies showed that texture reflecting the activated strengthening mechanisms, namely, surface relief, can alter surface topography significantly (Matsugaki et al, 2012;Matsugaki and Nakano, 2016;Uzer et al, 2016;Cicek et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent investigations revealed that osteoblast alignment is very important for the production of oriented BAp/ collagen structure. Osteoblast alignment can be achieved using metallic substrates with uni-directional periodic steps induced by plastic deformation [101,102] or laser-induced periodic surface structures (LIPSS) treatment [103], or collagen substrates with anisotropic molecular arrangement [104]. Osteoblastproduced collagen fibers and c-axis of precipitated BAp crystals show preferential orientation along the cell-elongated direction.…”
Section: Artificial Induction and Control Of The Bap Orientationmentioning
confidence: 99%